A Novel Homozygous Truncating Mutation in LAMB2 Gene in a Chinese Uyghur Patient With Severe Phenotype Pierson Syndrome - Zhu, Hong Tao; Maimaiti, Mireguli; Cao, Chen; Luo, Yan Fei; Julaiti, Delihuma; Liang, Lin; Abudureheman, Aizezi (Frontiers in Medicine, 2019)
【ABSTRACT】OBJECTIVE: Pierson syndrome (OMIM 609049) is a rare autosomal recessive disorder characterized by congenital nephrotic syndrome and complex ocular abnormalities. Severe renal symptoms had be associated with truncating mutations. Few Chinese patients from diverse ethnic background had been evaluated and reported with this syndrome. Here we report the first Uyghur patient with typical Pierson syndrome phenotypes and a novel pathogenic homozygous variant in LAMB2 gene. METHOD: A thirty-nine-day old Uyghur girl was born to consanguineous parents，the girl presented with general edema, severe hypotonia and bilateral microcoria. Laboratory tests revealed severe proteinuria, microscopic haematuria, hypoalbuminaemia，By the age of 74 days, she died of renal failure and respiratory infection.We detected on mutations of LAMB2 gene by the sanger sequencing. RESULT: Sanger sequencing detected a homozygous 2-bp deletion (c.2044_2045insTT/p.Cys682Phefs*13) in the exon 16 of LAMB2 gene. Both parents are heterozygous carriers. CONCLUSION: We reported the first Uyghur case of LAMB2 gene homozygous mutation leading to severe phenotype Pierson syndrome. The clinical presentation of the patient and the novel pathogenic variant detected in this patient added to the overall knowledge of this rare condition.